“Feeling Unsafe”: A Photovoice Analysis of Factors Influencing Physical Activity Behavior Among Malaysian Adolescents - Rosalia, Saimon; Wan, Yuen Choo; Awang, Bulgiba (Sage Publication, 2015)
Understanding the factors influencing physical activity (PA) in the Asia-Pacific region is critical, given the high prevalence of inactivity in this area. The photovoice technique explores the types of PA and factors influencing PA among adolescents in Kuching, Sarawak. A total of 160 photographs were collected from participants (adolescents, n = 22, mean age = 14.27 ± 0.7 years, and parents, n = 8, mean age = 48 ± 6.8 years). Data analysis used constant comparison methods of a grounded theory. The Analysis Grid for Environments Linked to Obesity was used to categorize PA factors. Study findings were centered on the concept of safety, facilities, parental restriction, friends, cultural traits, media, community cohesiveness, and weather. The central theme was “feeling unsafe” when being outdoors. To promote PA behavior, provision of PA facilities needs to be supported by other programs that build on peer support, crime prevention, and traffic safety, together with other educational campaigns.